Upregulation of brain-derived neurotrophic factor by Shiikuwasha (Citrus depressa Hayata) - Kensuke Nakajima; Shinya Okubo; Tomoe Ohta; Takuhiro Uto; Shigeru Oiso (BMC, 2023)
Abstract Background A reduction in the brain-derived neurotrophic factor (BDNF) level in the brain causes depression, whereas an increase in its level has therapeutic benefits against depression. BDNF is synthesized in various peripheral tissues and transported to the brain via the peripheral circulation across the blood-brain barrier. Therefore, substances that upregulate peripheral BDNF level may be used to prevent and treat depression. Previously, we demonstrated that Citrus unshiu peel (Chinpi) and C. natsudaidai increased BDNF level in a human renal adenocarcinoma cell line ACHN, which has BDNF-producing ability. Here, we evaluated whether Shiikuwasha (C. depressa Hayata), a citrus species cultivated in East Asia, can upregulate BDNF level in ACHN cells. Methods We evaluated the effects of test samples on BDNF production by measuring BDNF level in the medium of ACHN cells after a 24 h cultivation in the presence of test samples. The BDNF mRNA level was measured by quantitative reverse transcription-polymerase chain reaction, and the phosphorylation level of cyclic adenosine monophosphate response element-binding protein (CREB), a transcription factor regulating BDNF expression, was determined using Western blotting. Results We found that methanol extracts of Shiikuwasha peel, pulp, and seed increased the BDNF level in the culture medium of ACHN cells. Shiikuwasha peel and pulp extracts also upregulated BDNF mRNA level and phosphorylation of CREB. Conclusions These results suggest that Shiikuwasha includes the candidate antidepressant substances with peripheral BDNF-upregulation effect.